Contamination of Irrigated Soils with Toxic Substances and Protection of Them - Rahimberdievich, Asatov Sayitkul; oglu, Muhamadov Kamoriddin Mukhtor; Akhrorov, A. K. (Research Parks Publishing LLC, 2022)
Modernization of agriculture, irrigation and land reclamation, introduction of the latest achievements in crop production and agriculture, as well as the widespread use of fertilizers and pesticides, as well as the use of chemicals against pests and diseases require a rich and high yield of agricultural crops. . At the same time, the used chemical fertilizers and pesticides accumulate in the soil and form a dense layer under the plow, which impairs water, air permeability, metabolism, growth of microorganisms, and ultimately leads to deterioration of the ecological condition of soils.